Characterization, antibacterial, antioxidant, antidiabetic, and anti-inflammatory activities of green synthesized silver nanoparticles using Phragmanthera austroarabica A. G. Mill and J. A. Nyberg extract - Khodeer, Dina M.; Nasr, Ali M.; Swidan, Shady A.; Shabayek, Sarah; Khinkar, Roaa M.; Aldurdunji, Mohammed M.; Ramadan, Maryam A.; Badr, Jihan M. (Frontiers in Microbiology, 2023)
Introduction Diabetes mellitus is a chronic metabolic disorder that exhibited great expansion all over the world. It is becoming an epidemic disease adding a major burden to the health care system, particularly in developing countries. Methods The plant under investigation in the current study Phragmanthera austroarabica A. G. Mill and J. A. Nyberg is traditionally used in Saudi Arabia for the treatment of diabetes mellitus. The methanolic extract (200 mg/kg) of the plant and pure gallic acid (40 mg/kg), a major metabolite of the plant, as well as their silver nanoparticle formulae (AgNPs) were evaluated for their antidiabetic activity. Results and Discussion The results showed a decrease in body fat, obesity, an improvement in lipid profiles, normalization of hyperglycemia, insulin resistance, and hyperinsulinemia, and an improvement in liver tissue structure and function. However, the results obtained from AgNPs for both extract and the pure gallic acid were better in most measured parameters. Additionally, the activity of both the crude extract of the plant and its AgNPs were evaluated against a number of gram-positive, gram-negative bacteria and fungi. Although the activity of the crude extract ranged from moderate to weak or even non-active, the AgNPs of the plant extract clearly enhanced the antimicrobial activity. AgNPs of the extract demonstrated remarkable activity, especially against the Gram-negative pathogens Proteus vulgaris (MIC 2.5 μg/ml) and Pseudomonas aeruginosa (MIC 5 μg/ml). Furthermore, a promising antimicrobial activity was shown against the Gram-positive pathogen Streptococcus mutants (MIC 1.25 μg/ml).